The Influence of Discipline on Employee Motivation with Digital Attendance as a Moderator at the Karawang Regency Manpower and Transmigration Office - Ananda Pertiwi Nurbasari,; Mohammad Darul Fadli, Uus; Rosmawati, Ery (Research in Management of Technology and Business, 2025)
Digital technology advancements have significantly altered several organizational and daily routines. Employee discipline behaviour, including attendance, is influenced considerably by work motivation. High-motivation workers are typically more compliant with established guidelines and work schedules. With digital attendance as a moderating variable, this study examined how work discipline affected employee motivation. The Karawang Regency Manpower and Transmigration Office is the subject of this study, which uses a quantitative descriptive methodology. The study's population consisted of all 126 employees of the Karawang Regency Manpower and Transmigration Office. The research sample comprised 96 respondents, chosen using the Slovin algorithm with a 5% error rate. A questionnaire survey was used to gather data, and SmartPLS-4 software assisted in analyzing the PLS-SEM technique. In addition to the fact that digital attendance is a moderator that reinforces the association between work discipline and employee work motivation, the results demonstrated that work discipline has a positive and significant impact on work motivation.